Legal Analysis of the Disparity Between Indonesia's Legal Basis and Its Implementation in Protecting Human Rights - Idrus, Soleh; Aprita, Serlika; Asmara, Bima Sena Putra; Putra, M. Aidil (Jurnal Kepastian Hukum dan Keadilan, 2022)
The power that is held by human rights might be described as fundamental or basic in nature. People are able to more readily violate the rights of others since many people still do not understand how violation cases work. As a result, there are cases of violations that occur at the present time. A qualitative research method that takes an approach based on statutory regulation is the one that was used for this study. According to the findings presented in the conclusion, the protection and maintenance of human rights within the national institutional framework are established in institutions such as the National Women's Commission (Komnas Perempuan), the National Commission on Human Rights (Komnas HAM), and the Commission on Truth and Reconciliation. These institutions include the Indonesian Child Protection Commission (KPAI), the National Commission on Human Rights (Komnas HAM), and the Commission on Truth and Reconciliation (TRC). Despite this, the KKR was dissolved because it was seen to be incapable of performing its duties in an adequate manner.